1946: Can air or water be exploded?. (1st November 2020) - Bethe, H.A.
ABSTRACT: There has been much public discussion as to whether or not atomic bombs can start a nuclear chain reaction in the atmosphere. Similarly, since the planning of Navy atomic tests, many thoughtful scientists have expressed concern about the possibility of a chain reaction in water. It appears that atomic bombs of present construction are safe by enormous margins against igniting either the atmosphere or the water or the earth. There are good reasons to believe that even any conceivable future improvements of the bombs will still be safe in this respect.